Pengaruh Enviromentalism, Frugality, dan Status Sosial terhadap Niat Beli Thrifting dengan Brand Image sebagai Variabel Interveming pada Generasi atau Gen Z di Solo Raya - Ramadhan, Rio Rahmat; Mangifera, Liana (Masyarakat Ekonomi Syariah Bogor, 2024)
The influence of Enviromentalism, Frugality, and Social status on thrifting purchase intentions with Brand image as an Interveming Variable on generation / Gen z in Solo Raya. The aim of this research was to examine the impact of Environmentalism, Frugality, Social Status, and Brand Image as intervening factors on consumers' intentions to purchase thrifted items. Quantitative research methods were employed for this study. The sample for this research was selected using purposive sampling technique, resulting in a total of 129 respondents. The questionnaire was distributed among various groups, particularly students in the SOLO RAYA area, to ensure the reliability and validity of the instrument. The Partial Least Square (PLS) technique, facilitated by the SMART PLS 3.0 application, was utilized to analyze the data. The findings of this study indicate that Environmentalism significantly influences consumers' intentions to purchase thrifted items. Additionally, Frugality and Social Status were found to have a significant impact on thrifted purchase intentions. Moreover, Brand Image was identified as a significant mediator between Environmentalism, Frugality, and Social Status, and consumers' intentions to purchase thrifted items.